RESPON TANAMAN BAYAM (Amaranthus tricolor L.) TERHADAP PEMBERIAN BERBAGAI JENIS PUPUK ORGANIK PADA TANAH MARGINAL - Sriwani Punuindoong; Wiesje J.N. Kumolontang; Rafli I. Kawulusan (COCOS, 2017)
ABSTRACTThis study aims to determine the effect of giving various types of organic fertilizer tothe growth and production of spinach plants grown on the marginal soil and which type oforganic fertilizer the best is on the spinach plant. This research was conducted at the villageof Kalasey I for the pot experiment and the analysis of soil, manure and compost wasconducted at the laboratory of Soil Physics and the laboratory of Soil Chemistry and SoilFertility, Faculty of Agriculture Sam Ratulangi University of Manado. This research using byRandomized Block Design Method, where A as a control, B a manure of chicken, C a manureof cow, D a manure of pig, E a manure of goat and F as a compost. This study was conductedin 3 groups to obtain 18 pot experiments.The results showed that the application of various types of organic fertilizer on themarginal soil affected the availability of nutrients needed by plants in the growth andproduction of spinach plants in this case the height of the plant, the number of leaves, thefresh weight of the plant and the dry weight of the plant. Manure of goat provides the highestyield for height of the plant, the number of leaves, the fresh weight of the plant and dryweight of the plant.Keywords : Marginal Soil, Organic Fertilizer